The Role of Risk Management on the Effect of Asset Quality and Sustainability on Banking Financial Distress - Ismiantika, Ismiantika; Paramita, Ratna Wijayanti Daniar; Fadah, Isti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study examines the influence of asset quality, sustainability, and risk management on financial distress in banks registered with the Financial Services Authority (OJK) during the 2020–2023 period. Asset quality is measured by Non Performing Loans (NPL), sustainability by Green Loans, and risk management by the Capital Adequacy Ratio (CAR). A quantitative explanatory research method using Structural Equation Modeling (SEM) analysis was employed to test the direct and indirect relationships among the variables. The results indicate that NPL and Green Loans do not have a significant direct effect on financial distress but do influence risk management. Risk management itself does not directly affect financial distress but acts as an intervening variable that strengthens the relationship between sustainability and financial distress. Practical implications emphasize the importance of strengthening the integration of sustainability principles into risk management and developing more proactive asset quality management strategies to maintain banks' financial stability. This study provides theoretical and practical contributions to banking risk management and forms the basis for recommendations for regulators, bank management, and future research.